Nuclear architecture in the light of gene expression and cell differentiation studies - Bártová, Eva; Kozubek, Stanislav (Biology of the cell, 2006)
It is evident that primary DNA sequences, that define genomes, are responsible for genome functions. However, the functional properties of chromatin are additionally regulated by heritable modifications known as epigenetic factors and, therefore, genomes should be also considered with respect to their 'epigenomes'. Nucleosome remodelling, DNA methylation and histone modifications are the most prominent epigenetic changes that play fundamental roles in the chromatin-mediated control of gene expression. Another important nuclear feature with functional relevance is the organization of mammalian chromatin into distinct chromosome territories which are surrounded by the interchromatin compartment that is necessary for transport of regulatory molecules to the targeted DNA. The inner structure of the chromosome territories, as well as the arrangement of the chromosomes within the interphase nuclei, has been found to be non-randomly organized. Therefore, a specific nuclear arrangement can be observed in many cellular processes, such as differentiation and tumour cell transformation.
Keywords: buněčné jádro; exprese genu; buněčná diferenciace; lidé; regulace genové exprese; Cell Differentiation; Humans; Gene Expression Regulation; Cell Nucleus; Gene Expression